Intraoperative and Postoperative Complications of Three Dimensional (3D) Laparoscopic Cholecystectomy - Ubedullah Shaikh, Nawaz Ali Dal, Sikandar-E-Azam Yousfani, Muhammad Fareed Ullah Alvi, Arshad Hussain Abro (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the intraoperative and postoperative complications of three dimensional (3D) laparoscopic cholecystectomy. Methodology: This prospective observational study was carried out General Surgery Department of multiple hospitals of Sindh during the time period of 1st July, 2021 to 30th June 2022. Cholelithiasis were included in the study were included. The baseline and specific assessments in all patients, especially abdominal ultrasound for diagnosis of gallstone disease were done. All prepared were 3D laparoscopic cholecystectomy. Results: Sixty nine (88.46%) were females and 9(11.53%) were males with mean age was 37.32±4.03 years. Common intraoperative complications were gallbladder rupture observed in 3(3.84%) cases tight adhesions around gallbladder, bleeding from liver bed in 2(2.56%) cases. Post-operatively 4(5.12%) patients had nausea, postoperative fever in 5(6.40%) cases, port-site bleeding in 3(3.84%) cases and port site infection in 4(5.12%) cases. Conclusion: Intraoperative and postoperative complications are more common in patients with older age and male gender. Keywords: Intraoperative complications, Postoperative complications, 3D laparoscopic cholecystectomy